Balance in online social network structure - Cui, Ziqi (Nanyang Technological University, 2021)
Evaluating social network balance status can provide useful information for managing groups involving human entities. This project studies the methods of constructing the social network structure using signed graphs and extends the concepts of Heider’s balance theory in signed networks to analyze its characteristics. The balance degree can be computed according to Heider’s social balance theory and graph theory, which is a key property to measure the balanced state of a group in structure level. This project applies the online social networks datasets in signed structure and analysis of the network balance status by generating the balance degree, deriving corrective actions to change the balance degree to achieve the balance state.